Tafsir Jalal al-Din al-Suyuti dan Ibn Jarir al-Tabari pada al-Maidah/ 5: 51: Studi Tafsir Muqaran - Komarudin, Komarudin (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2022)
This article aims to reveal the interpretation of Jalaladdîn al-Suyûtî and Ibn Jarîr al-Tabarî about making Jews and Christians as leaders through their interpretation of the Qur'an in Surah al-Mâidah verse 51 and introduce the interpretation of muqāran. In fact, much literacy regarding to interpretations of al-Maidah verse 51 have been found, but among these literacies do not show the main source so that it feels far from substance. Helmy Zakaria for example, he wrote “Variety of Netizen's Interpretations About Non-Muslim Leaders; Study on the Interpretation of Surah al-Maidah verse 51